Statistical analysis of 12 years of standardized accelerated aging in photovoltaic‐module certification tests. (12th July 2021) - Gebhardt, Paul; Mülhöfer, Georg; Roth, Arnd; Philipp, Daniel
Abstract: Accelerated aging tests according to international standards (IEC 61215 and IEC 61730) have been used for many years to investigate photovoltaic (PV) module reliability. In this publication, we share a thorough analysis of the tests that were acquired over a time span of 12 years across a wide range of technologies and module generations. The results can serve as a valuable reference to evaluate the reliability of module types and prototypes beyond the use of standardized pass/fail criteria. Furthermore, this work can contribute to ongoing revisions of these standards. In more technical depth, we share the failure rates of different accelerated aging tests. We further discuss trends that are apparent over the investigated decade and reveal which test sequences have become the most relevant to differentiate different PV module types in terms of reliability. Abstract : Distribution of power loss after damp heat for 1000 h. In this publication, we share a thorough analysis of standardized tests that were acquired over a time span of 12 years across a wide range of technologies and module generations.